Cloud Computing And Its Financial Effects: Tax On Cloud - Turan, Metin (Information World, 2014)
In general, cloud computing is that software, platform and infrastructure as a service become available, and provide location independent access to these computing resources from anywhere, mostly via the Internet. Cloud computing has become widespread with development of Internet and its increasing use. This study aims to analyze the tax issue arising from cloud computing consumed or provided. In the study, institutions and organizations were examined due to cloud computing to which kind of tax they are subject and solutions recommendations were presented by indicating issues arised. In this context, the tax laws and secondary legislation were examined by content analysis and, it was seen that in Turkey, there were directly and indirectly some provisions in Tax legislation for cloud computing.